2021
DOI: 10.4315/jfp-20-326
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidence Supports the Use of Alcohol-Based Hand Sanitizers as an Effective Alternative to Hand Washing in Retail Food and Food Service Settings When Heavy Soiling Is Not Present on Hands

Abstract: Suboptimal food worker health and hygiene has been a common contributing factor in foodborne disease outbreaks for many years. Despite clear FDA Model Food Code recommendations for hand washing and glove use, food worker compliance with handwashing recommendations has remained poor for more than 20 years. Food workers’ compliance with recommended handwashing is adversely impacted by a number of barriers, including complaints of time pressure, inadequate number and/or location of handwashing sinks and handwashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 151 publications
(251 reference statements)
0
5
1
Order By: Relevance
“…Hand hygiene is an important means by which to reduce transmission of hNoV, the leading cause of acute viral gastroenteritis and also foodborne disease ( Scallan et al, 2011 ; Hall et al, 2013 ). While proper hand washing with soap and water is considered the gold standard hand hygiene intervention, it has been shown that compliance with handwashing requirements in certain food handling settings, such as restaurants, is low ( Allwood et al, 2016 ; Boyce and Schaffner, 2020 ). Although hand sanitizers are not a substitute for handwashing by food handlers in the retail food sector, they may be used by food handlers after performing a handwash, which has been shown to significantly improve the overall efficacy of the hand hygiene treatment ( Edmonds et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand hygiene is an important means by which to reduce transmission of hNoV, the leading cause of acute viral gastroenteritis and also foodborne disease ( Scallan et al, 2011 ; Hall et al, 2013 ). While proper hand washing with soap and water is considered the gold standard hand hygiene intervention, it has been shown that compliance with handwashing requirements in certain food handling settings, such as restaurants, is low ( Allwood et al, 2016 ; Boyce and Schaffner, 2020 ). Although hand sanitizers are not a substitute for handwashing by food handlers in the retail food sector, they may be used by food handlers after performing a handwash, which has been shown to significantly improve the overall efficacy of the hand hygiene treatment ( Edmonds et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study found that 60–80% of foodservice establishments were out-of-compliance for employee handwashing ( Verrill et al, 2021 ). Given the historical low compliance metrics with handwashing, and the fact that handwashing is the only permitted option for performing hand hygiene in retail food settings, there has been an interest in developing and evaluating alternative hand hygiene measures, including hand sanitizers ( Allwood et al, 2016 ; Boyce and Schaffner, 2020 ). Taken together, there is a clear need for fast, convenient, and effective hand hygiene treatments for hNoV control on human hands in food retail, processing, and harvesting environments.…”
Section: Introductionmentioning
confidence: 99%
“…The dependent variable was the total score of handwashing calculated by a questionnaire including four common questions during the survey years. The questionnaire consisted of contents related to the investigation of previous studies [29][30][31][32]. The handwashing behavior questions were about handwashing "before eating", "after toilet use", "after going out", and "with sanitizer", and scores were assigned from four points.…”
Section: Variablesmentioning
confidence: 99%
“…Since norovirus is responsible for most (58%) cases of foodborne illness of known etiology [ 50 ], causing 125 million (95% UI 70–251 million) cases globally [ 51 ], there have been studies to compare hand washing vs ABHR. There is clear evidence to support modifying the FDA Model Food Code to allow the use of EBHR as an alternative to hand washing when heavy soiling is absent [ 52 ]. Indeed, medical staff consider hand washing to be inadequate for hand hygiene, especially for bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%